Muatan Nilai Karakter Pada Buku Siswa Kelas IV Semester 1 Berdasarkan Profil Pelajar Pancasila - Aminatuzzuhriyyah; Fajar Setiawan; Lilik Binti Mirnawati (Universitas Sriwijaya in Collaboration with HDPGSDI (Himpunan Dosen PGSD Indonesia), 2023)
In the world of education, educators are not only required to convey knowledge, but also to instill character education so that they can form superior individuals in future social life. To support this, the government is promoting early childhood character education so that the nation's future children can become good individuals without breaking the law and taking Indonesia in a better direction in the future. This research aims to determine the content of character values in elementary school students' books based on the Pancasila Student Profile of the independent curriculum. This type of research is literature study, namely a series of activities related to library data collection methods through reading, recording and managing research materials. The data source that the researchers used was the Pancasila Education book for grade IV elementary school. Based on the results of the research that has been carried out, researchers can find the character values of Pancasila student profiles in elementary school students' books that have been analyzed, including Religious, Honest, Tolerant, Discipline, Hard Work, Creative, Independent, Democratic, Curiosity, Nationalism, Love of the homeland, Respect for achievements, Communicative, Love of peace, Love of reading, Care for the environment, Social care, and Responsibility. Thus, the researcher can conclude that all character values based on the Pancasila Student Profile appear to be dominated by the character values Love, Peace and Discipline which were discussed in semester 1.